Effect of Velocity on Dissolved Oxygen Cathodic Polarization using a Rotating Cylinder Electrode (Journal of Engineering, 2013)
The aim of the present work to study the effect of changing velocity (Reynold's number) on oxygen cathodic polarization using brass rotating cylinder electrode in 0.1, 0.3 and 0.5N NaCl solutions (PH = 7) at temperatures 40, 50 and 600 C. Cathodic polarization experiments were conducted as a function of electrode rotational speed and concentration.